Effect of undulators on magnet lattice and emittance - Victor Smaluk (Physical Review Accelerators and Beams, 2019)
NSLS-II is now one of the brightest synchrotron light sources worldwide, in user operations since 2014. Currently, 20 light-generating insertion devices (IDs) are installed: 3 damping wigglers and 17 undulators of various types. These devices introduce significant distortions into the magnet lattice of the storage ring. For each ID, the distortions have been locally corrected using quadrupole magnets located nearby the ID. The insertion devices have also a significant impact on the electron beam emittance. Precise measurements of the emittance were carried out at the Coherent Hard X-ray beamline for three different lattices: without IDs, with 3 pairs of damping wigglers only, and with all IDs. A minimum horizontal emittance of 0.76 nm was achieved. The radiation energy loss and relative energy spread were also measured using a streak-camera. The measured data show good agreement with analytical formulas and numerical simulations.